Diversidade morfológica do gênero loricaria linnaeus, 1758 na região hidrográfica atlântico nordeste ocidental - SARAIVA , Ananda Carolina Serejo (2019)
The genus Loricaria has a complex taxonomic history, marked mainly by the difficulty to delimit the species of the group due to the lack of knowledge about the morphological variations that these can present. In the Northeast Atlantic Hydrographic Region (RHANO), information on the variations among the populations of Loricaria is scarce. Therefore, this work aims to evaluate the morphometric variation between the populations of Loricaria in the RHANO basins, using traditional and geometric morphometrics techniques. Individuals from the Turiaçu, Mearim, Itapecuru and Munim river basins were used in this study. For traditional morphometry, 26 morphometric measurements were obtained using a digital caliper. For the geometric morphometry, each individual was photographed and 23 landmarks were selected. Both sets of data were submitted to Principal Component Analysis (PCA) and Canonical Variable Analysis (CVA). Different groupings were obtained according to the analysis performed. However, we point out that there are differences between the analyzed populations, especially those from the Itapecuru and Turiaçu basins. The main differences between these populations are found in the eyes, caudal peduncle and head shape. From the analysis of morphometry together with analysis of qualitative characters, we describe a new species of Loricaria valid for the Turiaçu river basin. The new species called Loricaria n. sp. "Turiaçu" differs from the other species mainly by the configuration of the abdominal plates. In this way, we conclude that the morphological variations observed among the populations of Loricaria in RHANO are due to the diversity of species in the region, but have not yet been fully delimited by taxonomic studies.